Rethinking scarcity and poverty: Building bridges for shared insight and impact - Blocker, Chris; Zhang, Jonathan Z.; Hill, Ronald Paul; Roux, Caroline; Corus, Canan; Hutton, Martina; Dorsey, Joshua; Minton, Elizabeth (Journal of Consumer Psychology, 2023)
AbstractResource scarcity is a powerful construct in social sciences. However, explanations about how resources influence overall wellbeing are difficult to generalize since much of the research on scarcity focuses on relatively affluent marketplace conditions, limiting its usefulness to large segments of the global population living in poverty. Conversely, poverty research provides cultural insights into resource deprivation, yet it stops short of explaining the systematic variation of scarce resources among impoverished individuals. To bridge these intellectual silos and advance a deeper understanding of scarcity, we integrate resource scarcity research, which builds upon a psychological tradition to understand various forms of everyday deprivation, with poverty research, which builds upon a sociological tradition to understand extreme and enduring deprivation. We propose a novel framework that integrates the concept of consumption adequacy and clarifies resource scarcity's forms, intensity, duration, and dynamic trajectories. We leverage this framework to generate a research agenda, and we propose ways to stimulate dialog among scarcity and poverty scholars, policymakers, and organizations to help inform impoverished life circumstances and generate effective solutions.